2015
DOI: 10.1021/am508836m
|View full text |Cite
|
Sign up to set email alerts
|

Nano Copper Oxide-Incorporated Mesoporous Carbon Composite as Multimode Adsorbent for Selective Isolation of Hemoglobin

Abstract: Assembly of nano-objects with tunable size, morphology and function into integrated nanostructures is critical for the development of a novel nanosystem in adsorption, sensing and drug/gene delivery. We demonstrate herein the fabrication of ordered mesoporous carbon by assembling uniform and highly dispersed copper-oxide (CuxOy) nanoparticles into the mesopores via evaporation of solvent from the mixture of triblock copolymer, carbon source and metal nitrate hydrate. The ordered 2D hexagonal mesoporous carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The pI of BSA is known to be ca. 4.9 [38]. BSA is positively charged as pH < pI; thus, the adsorption between BSA and the positively charged composite was hindered because of the electrostatic repulsion.…”
Section: Adsorption Behavior Of the Composite To Dnamentioning
confidence: 99%
“…The pI of BSA is known to be ca. 4.9 [38]. BSA is positively charged as pH < pI; thus, the adsorption between BSA and the positively charged composite was hindered because of the electrostatic repulsion.…”
Section: Adsorption Behavior Of the Composite To Dnamentioning
confidence: 99%
“…The results obtained by Lu et al indicated that nanomaterials consisting of selenium nanoparticles conjugated with folate (FA) are able to overcome multidrug resistance cancer cells [8]. The interesting application of nanoparticles was demonstrated by Zhang et al [9]. They have prepared porous composite consisting of mesoporous carbon and copper oxide nanoparticles for the purification of hemoglobin from human blood.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 or Ti 4+ were demonstrated to have higher binding selectivity to phosphopeptides . The copper oxide nanoparticle‐embedded mesoporous carbon composite exhibited selective adsorption to Hb under the synergistic effect of hydrophobic and metal‐affinity interactions . It follows that metal affinity interaction may provide contribution for binding selectivity to peptide and protein.…”
Section: Resultsmentioning
confidence: 99%